Quantitative Methods for Determination of Compositions of Kidney Stones Patients by Spectrophotometric Technique - Moaid Abid-Alwahid, Ali; Hassan kharnoob, Hussein; Ahmed Hasan, Hasan (Tikrit Journal of Pharmaceutical Sciences, 2023)
In this research chemical compositions (calcium, magnesium, and inorganic phosphorus ions) of kidney stones using quantitative methods were determined. Forty three calculi [14 from female (32.6%) and 29 of male (67.4%)] were investigated using visible spectrophotometry at different wavelengths. The analytical quantitative methods used for determination the concentrations of these metals were accurate, reliable and sensitive with linear range of (5-65), (0.05-0.5), and (1.5-13.5) μg/ml and standard deviation 0.004596, 0.002390, and 0.000756 and low detection limit (L.O.D.) was 0.1120, 0.0177, and 0.1890 μg/ml while the (RSD) was 1.40%, 2.36%, and 5.04% respectively.The most found kidney stones were either rigid or soft with different shapes and colures. The stones were digested with three solutions [1N HNO3, 16.5N HNO3, and de-ionized water (D.I.W)], the highest concentrations of the Ca, Mg, and P were found at 16.5N HNO3 digest solution.